Positive Impact On Environmental And Climatic Changes During Covid - Dr.Ruma Arora; Surbhi Jain; Manish Gome (Peneliti Teknologi Teknik Indonesia, 2023)
The rapid spread of a new corona virus (SARS-CoV-2) in China's Wuhan city in December 2019 has attracted international interest. Dry cough, high fever, body soreness, and exhaustion are some of the symptoms of a viral respiratory infection. Evidence suggests that environmental stressors like rising temperatures, increased pollution, and the COVID-19 pandemic may have a negative impact on mental health, potentially contributing to everything from short-term mood swings to long-term conditions like anxiety, depression, PTSD, and substance abuse. Numerous questions about the connections between the emergence of novel illnesses, environmental factors, climate, and human health were highlighted by the COVID-19 outbreak. Corona virus has had some bad effects on the world, but the crisis has had some positive effects on the environment as people have moved to prevent the spread of the virus. This has resulted in less pollution and less emissions of greenhouse gases.